2018
DOI: 10.1136/bmjspcare-2018-001543
|View full text |Cite
|
Sign up to set email alerts
|

‘Place bonding’ in children’s hospice care: a qualitative study

Abstract: BackgroundLimited knowledge exists of parents’ perceptions and experiences of children’s hospices and how these contribute to the varied access and uptake of services.AimThis study aimed to explore parents’ perspectives and experiences of a hospice, to understand the barriers and/or facilitators to accessing a hospice, and what characteristics parents wanted from hospice provision.MethodsA two-phase qualitative study underpinned by a constructivist grounded theory methodology was employed. Phase 1 used focus g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…From a more systemic perspective, there is evidence that the perception of safety and quality of care impacts how children and parents experience these transitional processes [ 61 , 67 , 90 , 91 , 114 , 124 ]. Similarly, policies to increase access to support services, as well as adequate socioeconomic conditions and the use of technological devices, are strategies associated with positive outcomes [ 52 , 59 , 60 , 65 , 74 , 116 , 123 , 125 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From a more systemic perspective, there is evidence that the perception of safety and quality of care impacts how children and parents experience these transitional processes [ 61 , 67 , 90 , 91 , 114 , 124 ]. Similarly, policies to increase access to support services, as well as adequate socioeconomic conditions and the use of technological devices, are strategies associated with positive outcomes [ 52 , 59 , 60 , 65 , 74 , 116 , 123 , 125 ].…”
Section: Resultsmentioning
confidence: 99%
“…The existence of several prejudices associated with the necessary healthcare and the negative progression of the disease can make it difficult for a child with a CCC and their parents to accept the condition, aggravating uncertainty about the future [ 53 , 55 , 60 , 64 , 65 , 67 , 89 , 93 , 96 , 106 , 126 – 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…Following this, to identify more focused codes and categories, an iterative process of constant comparison between the data and emerging analysis enabled codes to be sifted, sorted and compared to others identifying relationships, patterns and differences in the data set. Finally, following the three-staged grounded theory method of data analysis described by Charmaz (2014), final categories that represented the experience of the parents in this study were identified and informed the development of a theory of place bonding (Figure 1, Dunbar et al, 2018). The findings in this article focus on two elements of place bonding: parents’ experiences of identity and belongingness at the hospice.…”
Section: Methodsmentioning
confidence: 99%
“…This article reports the experiences of 24 parents of children with LLCs who participated in a larger two-phase grounded theory study (Dunbar et al, 2018) exploring the perceptions, experiences, barriers and facilitators and their influence on the access to one children's hospice in a region in England. During the planning stage of the study, a careful assessment of risk versus benefit was made and strategies identified to protect parents and children.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation